2012
DOI: 10.1210/jc.2011-2836
|View full text |Cite
|
Sign up to set email alerts
|

Serum Level of the Phosphaturic Factor FGF23 Is Associated with Abdominal Aortic Calcification in Men: The STRAMBO Study

Abstract: In healthy older men, circulating FGF23 is associated with parameters of mineral metabolism, including bone metabolism-regulating cytokines, and with severe AAC independent of traditional risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
56
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 63 publications
7
56
0
1
Order By: Relevance
“…37 An inverse relationship between CAC prevalence and BMD by DXA has also been shown in patients who are osteoporotic with normal kidney function and patients with HIV or metabolic syndrome. [38][39][40][41] In this study, a positive correlation was found between CAC SQRVand FGF23, which is in agreement with several published reports on vascular calcifications [42][43][44][45][46] but not in keeping with another report on patients with CKD not on dialysis. 29 Baseline FGF23 remained an independent predictor for baseline CAC after multivariable adjustment for age, CAD, diabetes, dialysis vintage, and BMD.…”
Section: Discussionsupporting
confidence: 92%
“…37 An inverse relationship between CAC prevalence and BMD by DXA has also been shown in patients who are osteoporotic with normal kidney function and patients with HIV or metabolic syndrome. [38][39][40][41] In this study, a positive correlation was found between CAC SQRVand FGF23, which is in agreement with several published reports on vascular calcifications [42][43][44][45][46] but not in keeping with another report on patients with CKD not on dialysis. 29 Baseline FGF23 remained an independent predictor for baseline CAC after multivariable adjustment for age, CAD, diabetes, dialysis vintage, and BMD.…”
Section: Discussionsupporting
confidence: 92%
“…FGF-23 is a phosphaturic hormone that regulates mineral homeostasis (7,24). Recent studies have suggested that FGF-23 is associated with incident cardiovascular disease, left ventricular hypertrophy (LVH), heart failure, progression of kidney disease, and mortality (6,7,25).…”
Section: Discussionmentioning
confidence: 99%
“…FGF-23 has recently emerged as a major phosphaturic hormone, and clinical trials demonstrate an association between FGF-23 levels and vascular calcification in both healthy and CKD populations (18,99). However, the addition of FGF-23 to cultured human VSMC did not increase the calcium content of the cells in either control or high-phosphate media (101).…”
Section: Risk Factors For Vascular Calcification In Ckdmentioning
confidence: 99%